Pathological changes in the atrial appendages of Mitral Stenosis Patients Operated - Orbegoso Rodríguez, Carlos M. (1961)
Since it was possible to operate commissurotomy in patients with mitral stenosis have been able to conduct examinations Biopsy member segments which were previously only studied in autopsy material. As a result there has been obtaining a number of new insights into various pathological aspects sometimes mean a radical change in the classical views.